Collagen type XV and the 'osteogenic status'. Issue 9 (22nd March 2017) - Lisignoli, Gina; Lambertini, Elisabetta; Manferdini, Cristina; Gabusi, Elena; Penolazzi, Letizia; Paolella, Francesca; Angelozzi, Marco; Casagranda, Veronica; Piva, Roberta
Abstract: We have previously demonstrated that collagen type XV (ColXV) is a novel bone extracellular matrix (ECM) protein. It is well known that the complex mixture of multiple components present in ECM can help both to maintain stemness or to promote differentiation of stromal cells following change in qualitative characteristics or concentrations. We investigated the possible correlation between ColXV expression and mineral matrix deposition by human mesenchymal stromal cells (hMSCs) with different osteogenic potential and by osteoblasts (hOBs) that are able to grow in culture medium with or without calcium. Analysing the osteogenic process, we have shown that ColXV basal levels are lower in cells less prone to osteo‐induction such as hMSCs from Wharton Jelly (hWJMSCs), compared to hMSCs that are prone to osteo‐induction such as those from the bone marrow (hBMMSCs). In the group of samples identified as 'mineralized MSCs', during successful osteogenic induction, ColXV protein continued to be detected at substantial levels until early stage of differentiation, but it significantly decreased and then disappeared at the end of culture when the matrix formed was completely calcified. The possibility to grow hOBs in culture medium without calcium corroborated the results obtained with hMSCs demonstrating that calcium deposits organized in a calcified matrix, and not calcium ' per se ', negatively affected ColXV expression. As a whole, our data suggest that ColXV may participate in ECM organization in the early‐phases of the osteogenic process and that this is a prerequisite to promote the subsequent deposition of mineral matrix.